2004
DOI: 10.1515/advg.2004.4.4.469
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of two classes of locally truncated diagram geometries

Abstract: Let G ¼ ðP; LÞ be a parapolar space which is locally A nÀ1; 3 ðKÞ for some integer n > 6 and K a field. There exists a class D of 2-convex subspaces, each isomorphic to D 5; 5 ðKÞ, such that every symplecton of G is contained in a unique element of D. Let G ¼ ðP; LÞ be a parapolar space which is locally A nÀ1; 4 ðKÞ for n ¼ 7 or an integer n d 9 and some field K.Assume that G satisfies the extra condition called the Weak Hexagon Axiom. Then there exists a class D of 2-convex subspaces, each isomorphic to D 6; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Theorem 5.3 has been suggested to me by the reading of a paper of Onofrei [14]. Onofrei aims to construct a D W5m -extension of a geometry Γ of type (A?,m)2,2> At that stage, she considers a sheaf for Γ', the completion of which is the required /)",",-extension.…”
Section: 5mentioning
confidence: 99%
“…Theorem 5.3 has been suggested to me by the reading of a paper of Onofrei [14]. Onofrei aims to construct a D W5m -extension of a geometry Γ of type (A?,m)2,2> At that stage, she considers a sheaf for Γ', the completion of which is the required /)",",-extension.…”
Section: 5mentioning
confidence: 99%
“…In a previous paper [8], we studied parapolar spaces Γ which were locally of type A n−1,4 (with n > 6 and n = 8) and which satisfied:…”
Section: Introductionmentioning
confidence: 99%
“…Using the fact that Γ inherits from the local structure two classes of maximal singular subspaces, a new family of objects D was constructed. The elements of D are 2-convex subspaces of type D 6,6 ; see [8,Theorem 2]. Second, using a sheaf theoretic argument it was shown that Γ was a homomorphic image of a truncated building; see [8,Theorem 3.b].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations